Pendekatan Inteligent Capital Dan Digital Literacy Terhadap Resiliensi Umkm, Studi Pada Daerah Pedesaan Di Purbalingga - Pratiwi, Agustin Riyan; Hendrawan, Martin; Wulan, Tyas Rahayu (Awatara Publisher, 2025)
Economic uncertainty highlights the importance of strengthening micro, small, and medium enterprises (MSMEs) resilience as a key pillar of a resilient economy. Existing studies on MSME resilience mainly emphasize external factors such as government policy, collaboration, and business strategies, while internal intangible resources remain underexplored. This study aims to analyze the effect of intellectual capital on MSME resilience, with digital literacy as a mediating variable. This research adopts a quantitative approach using survey data collected from rural MSME actors. Data analysis was conducted using multiple regression and mediation analysis. The results show that intellectual capital has a significant positive effect on MSME resilience. Intellectual capital also significantly influences digital literacy, which in turn positively affects MSME resilience, indicating that digital literacy partially mediates the relationship between intellectual capital and MSME resilience. These findings suggest that strengthening intellectual capital enhances MSME resilience both directly and indirectly through digital literacy. This study contributes to the literature by integrating intellectual capital and digital literacy into a resilience framework. Practically, the findings imply that MSME development policies should prioritize capacity building and digital literacy to foster sustainable resilience, particularly in rural areas.